PERAN BADAN PERMUSYAWARATAN DESA DALAM MENINGKATKAN DEMOKRASI LOKAL - Hajmi Fakhruri; Lina Marlina (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2020)
This research was aimed to describe how the role of the Badan Permusyawartan Desa in improving local democracy and to find out what are the obstacles of the Badan Permusyawaratan Desa in raising local democracy in the Desa Kramatlaban Kecamatan Padarincang Kabupaten Serang Provinsi. Banten. This research used qualitative research methods with data analysis techniques used which are descriptive qualitative. The subjects of this study were the Chairperson of the BPD Kramatlaban, the Secretary of the BPD Kramatlaban, Village head of the Kraatlaban, village secretary of the Kramatlaban and Kramatlaban Village community. The results of the study indicate that the BPD in Desa Kramatlaban has carried out its main tasks and functions, namely establishing Village Regulations with the Village Head, accommodating and channeling community aspirations, and carrying out the supervision of the performance of the Village Head properly. The obstacles of the BPD in carrying out its role are 2 (two) factors, namely internal and external factors. The following are internal factors: (1) Facilities, (2) Financial constraints, (3) Limited time. Whereas for external factors: (1) Less optimal participation from the community,. The efforts made by the BPD to improve local democracy are (1) Providing knowledge to the public about the importance of democracy, (2) Provide every information report on the implementation of the village community to the village government, and (3) Hold socialization with the community related to the functions and duties of BPD.